2013
DOI: 10.1002/cssc.201300328
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Homogeneous and Heterogeneous Catalysts for Glucose‐to‐Fructose Isomerization in Aqueous Media

Abstract: Herein, the first comparison of the mechanisms of glucose-to-fructose isomerization in aqueous media enabled by homogeneous (CrCl3 and AlCl3 ) and heterogeneous catalysts (Sn-beta) by using isotopic-labeling studies is reported. A pronounced kinetic isotope effect (KIE) was observed if the deuterium label was at the C2 position, thus suggesting that a hydrogen shift from the C2 to C1 positions was the rate-limiting step with the three catalysts. (13) C and (1) H NMR spectroscopic investigations confirmed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
154
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(168 citation statements)
references
References 51 publications
13
154
0
1
Order By: Relevance
“…These results clearly supported an intramolecular hydride shift mechanism catalyzed by AlCl3. 6,18 These results also indirectly explained that the coordination of Al with acyclic glucose on the C1-O and C2-O positions facilitated the following intramolecular C2 → C1 hydride shift.…”
Section: Acs Catalysismentioning
confidence: 74%
See 2 more Smart Citations
“…These results clearly supported an intramolecular hydride shift mechanism catalyzed by AlCl3. 6,18 These results also indirectly explained that the coordination of Al with acyclic glucose on the C1-O and C2-O positions facilitated the following intramolecular C2 → C1 hydride shift.…”
Section: Acs Catalysismentioning
confidence: 74%
“…This result proved that the hydride shift from C2 to C1 positions of glucose was the rate-limiting step. 6,18 As shown in Table S3, 40 it seemed that the concentration of AlCl3 had no 21 22 23 24...…”
Section: Acs Catalysismentioning
confidence: 96%
See 1 more Smart Citation
“…Isomerization of glucose to fructose or that of xylose to xylulose in water, catalyzed either by a heterogeneous catalyst like Sn-beta or by homogeneous catalysts like CrCl 3 /AlCl 3 , proceeds via ring opening of the glucose molecule and an intramolecular hydride shift Bermejo-Deval et al, 2012a;Choudhary et al, 2013a). Yang et al (2013) reported the mechanism of glucose isomerization into fructose on Sn-beta zeolite using DFT and the rate limiting hydride shift step was found to have a barrier of 77 kJ/mol.…”
Section: Carbohydrate Conversion Reactions: Isomerization Epimerizatmentioning
confidence: 98%
“…Basic homogeneous catalysts, however, tend to form higher amounts of by-products [17,25]. Very few works have been so far carried out using Lewisacid homogenous catalysts, and only two salts have been tested, CrCl 3 and AlCl 3 [27].…”
Section: Introductionmentioning
confidence: 99%